Correlates of stalking victimization in Canada: a model of social support and comorbidity - Cao, Liqun (International journal of law, crime and justice, 2020)
Research into stalking victimization has proliferated over the last three decades, but little research has been done with Canadian data and several theoretical questions related to stalking victimization risk remain largely unanswered. To address the gaps in the literature, this study advances an integrated approach of neighborhood social support from criminology and comorbidity model from health science to examine the correlates of stalking victimization. Relying on data from Canadian General Social Survey, results confirm that the correlation model is better justifiable than the causal model in exploring the relationships between risk factors and being stalked and that variables broadly derived from social support theory, such as community order and trust, are statistically significant correlates of stalking victimization. In addition, most variables in the comorbidity model are significant correlates of stalking victimization. We conclude that social contexts and individual life habits are both important for the risk of stalking victimization.